Communication strategy of The Regional Agency for Disaster Management of Sumbawa Regency in disaster mitigation - Anshori, Muhammad Syukron; Hatima, Husnul; Lestari, Ajeng (Faculty of Communication Sciences Universitas Padjadjaran, 2022)
Disaster management is needed to minimize the impact of disasters. It aims to prepare and educate people living in disaster-prone areas to be better prepared to respond to the impact of disasters. Sumbawa Regency is an area prone to natural disasters such as earthquakes, floods, fires, landslides, and others. The Regional Agency for Disaster Management (BPBD) of Sumbawa Regency is to implement a program called